Asuhan Keperawatan Pada Anak Dengan Diare - Zuraida Sukma Abdillah; IGA Dewi Purnamawati (AKPER Pasar Rebo, 2019)
BREAST MILK provides immune substances that have yet to be made by the baby so baby drinking BREAST MILK more rarely ill especially at the beginning of his life. Components of the anti-infective substances in BREAST MILK protects babies from a variety of infections, caused by bacteria, viruses and other antigens. The Disease is often suffered by children namely digestive problems such as diarrhea or gastroenteritis. Diarrhea is a symptom that occurs because of a disorder that involves the digestive functions, absorption and secretion. Diarrhea caused by the transport of water and electrolytes that are abnormal in the intestine. Complications that can occur include dehydration, cardiovascular system disorders due to heavy hipovolemia, seizures due to high fever especially in Shigella infection, perforated the intestine due to typhoid fever, vomiting and death. The purpose of writing expected of students able to provide nursing care in children experiencing diarrhea. The method of writing is descriptive or description of a case and the library. The results of this scientific paper is a student gain an overview of nursing care in children with diarrhea. Nursing problems include: Airway ineffective, Hipovolemia, nutritional Deficits, the risk of infection, impaired growth development